Improving durability and predictability of boron steel components - Lehtilä, Toni (My University, 2025)
This thesis work focuses on improving durability and predictability aspects of boron steel components used in the traction solution industry. The thesis starts with an introduction of the company Nordic Traction and its products. The key properties of boron steel, like high hardness and wear resistances are explained and introduced. Manufacturing processes and additional procedures in the industry have remained quite stagnant for a while, so more optimized and recent methods can be beneficial for the company. This thesis work is a literature review, where the research to enhance boron steels are found from scientific articles and studies globally. Key findings of the thesis can be divided mainly into two parts: heat treatment procedures, and surface treatments or coatings. Heat treatment procedures consist of cryogenic treatments, subcritical annealing and hardening, and quenching and partitioning. Coating portion focuses on the laser cladding principle which is compared to case hardening and protective paintings. All the previously mentioned processes showed significant increases to wear resistances and hardness values of boron steels, but the required additional machinery, knowledge, energy costs, and lack of research data specifically tailored on boron steels still offer some challenges in the industry.

Tämä diplomityö keskittyy booriteräksen kestävyyden ja ennustettavuuden parantamiseen erilaisissa pitoa parantavissa ketjuissa sekä oheiskomponenteissa. Työ alkaa Nordic Traction yrityksen sekä sen valmistamien tuotteiden esittelyllä. Booriterästen tärkeät ominaisuudet, kuten kovuus ja kulutuskestävyys selitetään myös tarkemmin. Valmistusprosessit ja lisätoimenpiteet tässä teollisuuden haarassa ovat säilyneet muuttumattomina suhteellisen kauan, joten yhä optimoidummat ja nykyisemmät metodit voivat olla yritykselle kannattavia. Tämä diplomityö on kirjallisuuskatsaus, jossa booriterästen tehostamiseen käytetty tutkimusmateriaali on kerätty tieteellisistä artikkeleista ja tutkimuksista ympäri maailman. Tärkeimmät löydökset voidaan jakaa pääasiallisesti kahteen osaan: lämpökäsittelymenetelmiin, sekä erilaisiin pintakäsittelymenetelmiin. Lämpökäsittelymenetelmät koostuvat muun muassa kryogeenisestä käsittelystä, subkriittisestä hehkutuksesta ja kovettamisesta, sekä osittaiskarkaisusta. Pintakäsittelymenetelmät keskittyvät puolestaan laserpäällysteisiin, joita verrataan pintakarkaisuun ja suojaaviin maaleihin. Kaikki edellä mainitut toimenpiteet onnistuivat tehostamaan booriterästen kulutuskestävyyttä sekä kovuutta merkittävästi, mutta niiden vaatima mahdollinen lisäkoneisto, osaaminen, energiakustannukset, tai erityisesti booriteräksillä tehdyn tutkimusdatan puute tarjoaa osansa teollisuushaaran haasteista.
Keywords: boron steel, traction solution, wear resistance, heat treatment, laser cladding